Impact of Audio-Visual Education on Knowledge of Diabetes Patients - Puspita, Ranti; Anggraini, Rima Berti; Maryana, Maryana (Genius Journal, 2026)
Introduction: Diabetes mellitus is a chronic metabolic disease with a rapidly increasing prevalence worldwide and remains a major public health challenge due to its long-term complications and management demands. Effective diabetes self-management education, particularly through audio-visual approaches, is essential to improve patients’ knowledge and support optimal disease control. Objective: Diabetes Mellitus (DM) is a metabolic disease characterized by elevated blood glucose levels, caused by damage to insulin secretion, insulin function, or both. The purpose of this study was to determine the effect of audiovisual education on Diabetes Self-Management Education (DSME) on improving the knowledge of diabetes mellitus patients at Junjung Besaoh Regional Hospital, South Bangka in 2025. Method: This study used a pre-experimental study with a one-group pretest-posttest design. The sampling technique used purposive sampling with 18 respondents. Data collection used the 24-question DKQ 24 (Diabetes Knowledge Questionnaire). Data analysis used the Wilcoxon test Result: The results of this study demonstrate that the mean knowledge score of respondents before receiving DSME education through audiovisuals was 43.02 (SD=7.569). After the education, the mean knowledge score of respondents increased to 82.13 (SD=5.425), with a difference of -39.117 (SD=7.847) between the pre- and post-education levels. There was an effect of Audiovisual Diabetes Self-Management Education (DSME) on improving the knowledge of diabetes mellitus patients at Junjung Besaoh Regional Hospital, South Bangka in 2025 (p<0.05). Conclusion: The results of this study suggest that healthcare services can adopt DSME audiovisual media as a primary strategy in diabetes education, especially for complex materials such as DSME. This media has proven effective in improving respondents' understanding and can be applied in various healthcare services.